Effect of cilofungin on the growth and metabolite production in spirulinasp and chlorellasp - JAGANNATHAN. N,; PRATHAP.P,; SUKUMARAN.N, (International Journal of Pharma and Bio Sciences, 2016)
A novel strategy of using an antifungal cilofungin to alter the algal metabolics for increased production of biomass, fat, protein and other metabolites were inferred. The effect of varying concentrations of cilofungin (0.02% to 0.1%) on unialgal cultures of Spirulina sp. and Chlorella sp. isolated from ennore estuary, Chennai, an highly polluted coastal ecosystem in India was investigated. Various parameters like cellular growth, dry mass, carbohydrates, proteins, fatty acids, chlorophyll and carotenoids were assessed with respect to time. At a given cilofungin concentration of 0.08% in Spirulina sp and 0.06% in Chlorella sp, an increase in protein content from 421mg/g to 655mg/g and 430mg/g to 646 mg/g of biomass, an increase in fat content from 57mg/g to 74 mg/g and 75 mg/g to 90mg/g of biomass was obtained in comparison to their mother cultures with a simultaneous increase in their biomass concentration from 1.09g/l to 1.5g/l and 1 g/l to 1.23g/l respectively, whereas the carbohydrates were gradually decreased in cilofungin treated cultures. This study thus analyse the effect of cilofungin in algae, inhibiting the glucan production and inducing the alternate metabolic pathways in Spirulina sp and Chlorella sp. for lipid and protein accumulation.